HIV-1 subtype distribution and drug resistance profiles among PLWHA with detectable viremia in Henan Province, China, 2023 - Jinjin Liu; Chaohong Fu; Xuan Yang; Xiaohua Zhang; Shuguang Wei; Jie Ma; Qingxia Zhao; Yuqi Huo (Scientific Reports)
Abstract In China, Henan Province is a region with a high HIV burden. Furthermore, drug resistance (DR) among people living with HIV/AIDS (PLWHA) on antiretroviral therapy (ART) is becoming a critical barrier to achieving viral suppression. Monitoring DR in PLWHA with detectable viremia after ART is crucial, especially given the widespread use of NNRTI and NRTI, which have historically been the backbone of China’s national ART program due to affordability and availability. In this study, plasma samples from PLWHA with viral load (VL) ≥ 40 copies/mL after ≥ 6 months of ART from January 2023 to December 2023 were collected for genotypic DR testing. Of 804 individuals with detectable viremia, a total of 14 HIV-1 subtypes were detected. The top five subtypes were B (55.97%, 450/804), CRF01_AE (22.14%, 178/804), CRF07_BC (15.42%, 124/804), CFR55_01B (3.36%, 27/804), and CRF08_BC (1.00%, 8/804). DR analysis revealed a prevalence of 67.79% (545/804). The resistance rates for non-nucleoside reverse transcriptase inhibitors (NNRTIs), nucleoside reverse transcriptase inhibitors (NRTIs), protease inhibitors (PIs), and integrase strand transfer inhibitors (INSTIs) were 62.94% (506/804), 53.23% (428/804), 7.34% (59/804), and 3.98% (32/804), respectively. The prevalence of DR among PLWHA below and ≥ 200 copies/mL were 40.63% (13/32) and 68.91% (532/772), respectively. Multivariate regression analysis showed that age < 29 years and 40–49 years, baseline CD4 count < 500 cells/µL, current VL of 103–105 copies/mL, and initial ART regimen of NRTIs + NNRTIs were closely associated with the occurrence of DR. These findings highlight the urgent need for expanded access to drug resistance testing and the adoption of WHO-recommended regimens, such as dolutegravir (DTG), to mitigate the growing threat of DR. Our results suggest that drug resistance testing should be applied to all PLWHA with detectable viremia, and treatment strategies should be optimized to align with global guidelines.